E-courtship a descriptive study - Panganiban, Pamela Concepcion 1986-; Manalili, Perlita G. (2012)
"This study attempted to determine the means by which Social Networking Sites (SNSs), Facebook, Twitter, and Yahoo Messenger in particular, serve as venues for modern-day courtship between 16 to 30 years old Filipino teens and young adults. The study framework integrated Ludwig van Bertalanffy's System Theory, Marshall McLuhan's Technological Determinism Theory, and Elihu Katz and Jay Blumler's Uses and Gratifications approach to serve as basis for this research endeavor. A triangulation research method approach was also taken, using both survey questionnaire and focus interviews, in gathering the data required for the study. The survey was administered to 300 respondents, equally divided into the online and traditional groups, while three experts were interviewed regarding the subject matter. Results showed that Filipino teens and young adults are highly exposed to SNSs and have welcomed, accepted and embraced various modern ways - including the digital forms - of courtship and dating. However, despite this positive reception, the surveyed individuals revealed that they are partial to and still preferred the traditional means of pursuing their love interest or object of attraction."
Vita.
Undergraduate thesis (A.B. Broadcast Communication)--University of the Philippines, Diliman.
Keywords: Online social networks; Courtship -- Communication systems; Computer networks